Revisiting the Mirzanama: Class Consciousness and the Mughal Middle Classes. (May 2023) - Gupta, Riya
Drawing on earlier scholarship that argues for the existence of the middle classes in the Mughal Indian society, this article aims to render their sociocultural history more visible through a re-examination of the Mirzanama. The text, often associated with the elite, on the contrary, addresses the middling petty officialdom, advising them on micro-aspects of their sociocultural lives such as the etiquette of dining. Read imaginatively, the advisory reveals class consciousness—in terms of being distinct from both the nobility and the common populace—to be an important factor defining the middle-class way of life. Significantly, a micro-historical reflection, macro-historically helps us challenge the recently created dichotomy, in historical scholarship, between the elite and the non-elite, by reasserting the presence of sufficiently conscious middle strata.